Presidential power : forging the presidency for the twenty-first century - Shapiro, Robert Y., 1953-; Kumar, Martha Joynt; Jacobs, Lawrence R. (Power, conflict, and democracy., 2000)
Richard Neustadt's seminal work Presidential Power: The Politics of Leadership has endured for nearly four decades as the core of academic study of the American presidency. Now, building on and challenging many of the arguments in Neustadt's wo.